Bonus depreciation as instrument for structural economic policy: Effects on investment and asset structure - Sebastian Eichfelder; Jonas David Knaisch; Kerstin Schneider (Arbeitskreis Quantitative Steuerlehre (arqus), 2025)
We analyze how the expiration of a regional bonus depreciation regime in eastern Germany (Development Area Law, DAL) affected real investments and asset structures of establishments in the manufacturing sector. Our rich administrative data allow us not only to identify the aggregate effect, but also to determine which types of investments and firms are most affected. Our baseline results indicate that the DAL increased real aggregate investment by 16.0% to 19.9%. This effect is stronger for investments in buildings (76.6% to 92.9%) with long regular depreciation periods and land (108.0% to 121.3%) that cannot be depreciated regularly. The impact on equipment investment is much smaller (7.3% to 10.5%). Thus, firms not only increased real investment, but also adjusted their asset structure in response to the policy. We observe significantly stronger investment responses for large firms with lower tax planning and compliance costs and multi-establishment firms with more opportunity for subsidy shopping. However, we do not find evidence that firms with higher financial reporting costs (i.e., incorporated firms and firms without an active business owner) show a weaker investment response.
Keywords: G11; H25; H32; M41; 330; bonus depreciation; real investment; user cost of capital; tax elasticity